Polar Cartilages and Formation of Crista Sellaris in Grass Snake, Natrix natrix (Ophidia, Colubridae), Chondrocranium at the Early Stages of Embryogenesis - Sheverdyukova, H.V. (Вестник зоологии, 2012)
The initial developmental stages of grass snake’s, Natrix natrix Linnaeus, 1758 chondrocranium are described. Three paired structures form the floor of N. natrix’s neurocranium: cranial trabeculae, polar cartilages, and parachordals. The primordiums of polar cartilages and their independent centers of chondrification are identified at the stage 26 of development for the first time for N. natrix and snakes in general. The participation of these structures in the formation of crista sellaris and carotid foramina is proved. Описаны начальные этапы развития хрящевого черепа Natrix natrix Linnaeus, 1758. Три парные структуры: черепные трабекулы, полярные хрящи и парахордалии образуют дно нейрокраниума N. natrix. Зачатки полярных хрящей и их независимые центры охрящевения определены на 26-й стадии развития впервые для N. natrix и змей в целом. Доказано участие этих структур в формировании crista sellaris и сонных отверстий.